The Effect of Organic Liquid Fertilizer of Rice Washing Water and Goat Urine on the Growth of Romaine Lettuce (Lactuca sativa. Var. longifolia) using the Hydroponic Method - Tobing, Joshua (12th International Scholars Conference 2025, 2026)
Hydroponics, an emerging agricultural technology, allows the cultivation without soil, but using nutrient-rich water instead. This is promising for future agriculture, as it can be applied in various locations and yields higher-quality production results, thereby increasing market competitiveness. Additionally, waste materials such as rice washing water and goat urine can be repurposed as valuable organic fertilizers. Rice washing water is rich in nutrients such as vitamin B1, phosphorus, calcium, and nitrogen, and is a liquid organic fertilizer promoting superior plant growth. Goat urine, containing natural phytohormones, supports root and shoot development, making it a useful alternative to organic fertilizers. Research indicates that liquid organic fertilizers are often preferred over synthetic options in hydroponic systems due to their high content of bioactive compounds and environmental safety. This study focuses on Romaine Lettuce (Lactuca sativa. Var. longifolia) cultivation using various nutrient treatments, including rice washing water, goat urine, and AB Mix, with measured concentrations ranging from 1000 to 1400 parts per million (PPM). The results show significant differences in growth among the treatment groups, with AB Mix producing the highest in plant height, number of leaves, and leaf width, thus indicating the effectiveness of nutrient type on plant development.